Morphological variation in fruits of piquin pepper genotypes (Capsicum annuum var. Glabriusculum) from Northeast and Central Mexico - Alcalá-Rico, Juan Samuel Guadalupe Jesús; Ramírez-Meraz, Moisés; Maldonado-Moreno, Nicolás; Borja-Bravo, Mercedes; Camposeco-Montejo, Neymar; López-Benítez, Alfonso (Ecosistemas y Recursos Agropecuarios, 2023)
The objective was to determine the morphological variation of fruits of piquin pepper genotypes and to define fruit descriptors to identify and discriminate this species. Ten genotypes were used and 24 morphological characters related to the fruit were considered. Differences (p ≤ 0.01) were observed in the source of variation genotypes for most quantitative characters. Genotypes G6 and G7 presented the highest values in fruit length, fruit length/diameter ratio and predominant number of locules. Based on similarity, genotypes were clustered into six and four groups for quantitative and pseudo-qualitative characters, respectively. Principal components determined that fruit diameter, fruit length, fruit length/diameter ratio, color intensity before maturity, color before maturity, fruit shape, and apex shape were the most discriminatory, allowing a morphological description and identification when only fruit- elated characters are known.